2018
DOI: 10.2147/tcrm.s176281
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intramuscular neostigmine to accelerate bladder emptying after spinal anesthesia

Abstract: PurposePostoperative urinary retention (POUR) is one of the most common complications following spinal anesthesia. Spinal anesthesia may influence urinary bladder function due to interruption of the micturition reflex. Urinary catheterization is the standard treatment of POUR. Urinary catheter insertion is an invasive procedure, which is associated with catheter-related infections, urethral trauma, and patient discomfort. The purpose of this study was to determine the effectiveness of intramuscular (IM) neosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…When it comes to the primary outcomes of the current study, the times to first voiding after treatment and after catheter removal showed significant reduction with IM administration of neostigmine (P = 0.027 and 0.036, respectively). In agreement with our findings, Senapathi and colleagues reported that times to first voiding after spinal anesthesia and after treatment were significantly reduced with neostigmine administration [9] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…When it comes to the primary outcomes of the current study, the times to first voiding after treatment and after catheter removal showed significant reduction with IM administration of neostigmine (P = 0.027 and 0.036, respectively). In agreement with our findings, Senapathi and colleagues reported that times to first voiding after spinal anesthesia and after treatment were significantly reduced with neostigmine administration [9] .…”
Section: Discussionsupporting
confidence: 93%
“…Transmission of efferent and afferent action potentials on the nerve fibers of S2-S4 spinal cord segments to and from the UB is inhibited by spinal injection of anesthetic medication [9] . Inhibiting the transmission of afferent nerve fibers from the UB to the micturition center in the brain results in analgesia of the UB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, one can consider a chance for new indication areas for formulations with standardized and sufficiently high alkaloid content. Peripheral reduction of AChE activity was suggested for treatment of urinary retention or myasthenia gravis [28,29]. In case of sufficient delivery across the blood-brain barrier, the alkaloids might extend the spectrum of drugs used for therapy of central dysfunction of the cholinergic system, e.g., early stages of Alzheimerʼs disease or other forms of cognitive decline.…”
Section: Contraction Force (%)mentioning
confidence: 99%